Gambaran Sikap Keluarga Tentang Pencegah Penyakit Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Piyungan Bantul - Tejo Krista Timor; Jenita Doli Tine Donsu; Sarka Ade Susana (Poltekkes Kemenkes Yogyakarta, 2017)
Pneumonia or acute pulmonary parenchymal infection is a health problem and the biggest contributor of death in toddlers (children under five years). Toddler period is a period where children are very active. With a variety of activities that they want to do, it can reduce appetite that can make them more susceptible to especially infection disease. One of family functions is health care in which they function to carry out health care practices including preventing health problems. This research study aimed to know the attitudes of family about prevention of pneumonia disease in toddlers. This research study was a descriptive research study with survey method in 2017. The subjects of this research study were family who have child/children under five years old with a history of pneumonia in 2016, that were 61 people. The sampling technique was purposive sampling (data collection using questionnaires). The research study used questionnaire. The data analysis used frequency distribution and it was presented in tables. The results of this research study showed that 57,4% of the respondents had a positive cognitive, 52,5% of them had a positive affective and 54,1% of them had a positive conative. The description of family attitude about prevention of pneumonia disease in toddlers had 54,1% positive attitude. The family positive attitude was supported by 5 out of 10 (50%) statements on the questionnaires that were answered with positive category. The conclusion from this research study was that attitude and the components forming attitude, consisting of cognitive, affective and conative, was positive.